CONTROLLED VERSUS UNCONTROLLED VIRTUAL REALITY: PSYCHOPHYSICAL RESPONSE - Kurapov, Anton; Dubynskyi, Oleksii; Balashevych, Oleksandra; Tsurikova, Hanna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
Virtual reality gains popularity due to its wide range of applications, starting with entertainment and ending with a whole set of educational programs. It surely has its positive sides and drawbacks. The current study focuses on the evaluation of the psychophysical response to the ability to control and manipulate virtual reality. It also focuses on the impact virtual reality has on the ability to perform spatial modeling. The study’s sample includes 140 participants. The research has form of a classic experiment involving two experimental groups and one control group. While the second experimental group consisted of 40 respondents and could only observe virtual reality without being able to influence their actions in it, the first experimental group consisted of 44 participants who could control their actions in virtual reality (they could move, jump and choose places from which you could look at nature in virtual reality). The control group only passed the proposed tests measuring spatial modeling skills and was not involved in virtual reality. Psychophysical response was measured using a polygraph. The results show that being able to control VR makes the experience more immersive, increasing emotional response and stress, while not being able to control it causes less stress and engagement. The conclusion is that short virtual reality sessions have a positive effect on the ability to perform spatial modeling tasks